School Management System (Center for Research and Development): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Center For Research and Development (CRAD) is a web-based platform under SchoolManagement System 2 to manage all aspects of Research, such as research studydocuments, research defense, research festival, and research payment transactions. Theresearch department of Bestlink College of the Philippines was experiencing manualtransactions and spending more amount of time, but with the use of this system, the users willbe able to use an automated system to find past research studies and check researchpayment transactions. The main objective of the researchers is to create a system that willhelp the staff and students complete the transactions faster by using an automated systeminstead of a manual.The researcher’s team results in more opportunities for clients that meet their needs anddemands. The proponents successfully created a system that can truly help and eventually beable for research department to process their work. As a result, the client needs an automationsystem that is less time-consuming for research department transactions instead of a manualprocess. DiscussionAs interviews were performed by the team, Bestlink College of the Philippines Center ForResearch and Development (CRAD) has no automated system; it is time-consuming tomanage transactions. The staff of the research department uses a manual way to process allthe transactions, from collecting information to monitoring reports. In this research, theresearcher will focus on developing a web-based for the research department. The mainobjective is to help the students, teachers, and staff provide a secure platform web-basedsystem for automated transactions.
Keywords: IT & Management